The first skin cancer screening day at the Italian parliament: a Euromelanoma initiative. (29th July 2014) - Suppa, Mariano; Neri, Luca; Bianchi, Luca; Capizzi, Rodolfo; Carbone, Angelo; Catricalà, Caterina; Chimenti, Sergio; Fargnoli, Maria Concetta; Fossati, Barbara; Frascione, Pasquale; Peris, Ketty
Abstract Background The effort to decrease incidence/mortality of skin cancer should target not only the general public but also politicians and decision makers, to create a proper health policy. We report the results of the first Skin Cancer Screening Day at the Italian Parliament, organized to draw politicians' attention on skin cancer. Methods A questionnaire was used to collect data on participants' characteristics and suspected skin cancers. Results We screened 70 members of parliament (61.4% males, median age 54 years). Overall skin cancer suspicion rate was 14.5%. Suspicion rate, detection rate, and positive predictive values for melanoma were respectively 1.6, 1.6, and 100%, and for basal cell carcinoma 6.5, 1.6, and 25%. Highly educated, <54‐year‐old females reported sun‐seeking behaviors. Conclusions The considerable suspicion rate produced by this screening is justified by the particular demographics of the study population. Italian members of parliament display sun‐seeking behaviors similar to those previously described in the general public. Increasing politicians' attention on skin cancer is vital for sufficient resources to be allocated to prevention strategies. Expert medical groups and politicians should cooperate to create a proper, integrated policy on skin cancer.